2022
DOI: 10.1002/cnm.3609
|View full text |Cite
|
Sign up to set email alerts
|

A coupled computational framework for bone fracture healing and long‐term remodelling: Investigating the role of internal fixation on bone fractures

Abstract: In this study, a coupled computational modelling framework for bone fracture repair is presented that enables predictions of both healing and remodelling phases of the fracture region and is used to investigate the role of an internal fixation plate on the long-term healing performance of a frac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…While E is reduced from 110 to 100 GPa, the healing performance increases from .126 to .131, the difference of which is only .005. Although smaller E can make H at the 120th higher, Quinn et al 52 have found that even though there is no bone plate fixation, the formation of a bony bridge can still occur under reasonable load conditions. When fixing the fracture, the most important things are to achieve effective reduction and maintain a certain fixation stability.…”
Section: Resultsmentioning
confidence: 99%
“…While E is reduced from 110 to 100 GPa, the healing performance increases from .126 to .131, the difference of which is only .005. Although smaller E can make H at the 120th higher, Quinn et al 52 have found that even though there is no bone plate fixation, the formation of a bony bridge can still occur under reasonable load conditions. When fixing the fracture, the most important things are to achieve effective reduction and maintain a certain fixation stability.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that the mesenchymal stem cells origin from the surrounding tissues, periosteum and trabecular bone ( Fig 2 ). In order to avoid too fast stiffening of the regions next to the callus borders, similarly as in [ 42 ], the concentration at the boundaries varies in time such that the maximum value is reached after ca. 3 weeks c bound = 1.0− exp (− t /4) [days], (see Fig 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has to be emphasized, that usually in studies employing similar finite element model (FEM) [ 33 , 42 ], the poroelastic tissues are considered as fully saturated. However, in the present study a partial saturation is assumed to account for the capillary effects.…”
Section: Methodsmentioning
confidence: 99%
“…Weight and bulk [28] Metallic bone plates can add weight and bulk to the surgical construct, which can be a concern in certain cases, particularly for pediatric patients or when implants are used in weight-bearing areas.…”
Section: Exploration Of Innovative Techniques and Materialsmentioning
confidence: 99%